2022
DOI: 10.3390/ijms231710101
|View full text |Cite
|
Sign up to set email alerts
|

Incretins as a Potential Treatment Option for Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is a metabolic disease affecting an increasing number of pregnant women around the world. It is not only associated with numerous perinatal complications but also has long-term consequences impacting maternal health and fetal development. To prevent them, it is important to keep glucose levels under control. As much as 15–30% of GDM patients will require treatment with insulin, metformin, or glyburide. With that in mind, it is crucial to keep searching for novel and improved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
4

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 66 publications
0
5
0
4
Order By: Relevance
“…Furthermore, a large percentage of such pregnancies require delivery by cesarean section. Persistently elevated maternal blood glucose also affects the developing fetus, causing excessive production of fetal insulin, resulting in a higher incidence of macrosomia and birth trauma [37,38]. Many studies have found an increased risk of macrosomia also in children of mothers with EGWG [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a large percentage of such pregnancies require delivery by cesarean section. Persistently elevated maternal blood glucose also affects the developing fetus, causing excessive production of fetal insulin, resulting in a higher incidence of macrosomia and birth trauma [37,38]. Many studies have found an increased risk of macrosomia also in children of mothers with EGWG [39][40][41][42].…”
Section: Discussionmentioning
confidence: 99%
“…GDM is one of the most common diseases that occur during pregnancy and has long-term effects on the mother and her offspring by increasing the risk of developing metabolic diseases in the future. GDM is a condition of glucose intolerance diagnosed for the first time during pregnancy without a known history of glucose metabolism disorders before [16,24]. EGWG is diagnosed by exceeding the recommended weight gain depending on pre-pregnancy weight according to the IOM 2009 criteria [7].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials studying the effect of DPP-4 inhibitors on GDM have demonstrated a reduction in insulin resistance, alleviation of the symptoms associated with hyperglycemia, reduction in fasting plasma glucose and serum insulin, and downregulation of a biomarker indicative of glucose intolerance [15]. While more research is needed to understand the role of DPP-4 in GDM, the existing literature suggests that DPP-4i (i.e., gliptin) therapy could help mitigate the capacity of GDM to program the fetus for future obesity and metabolic disease [16].…”
Section: Introductionmentioning
confidence: 99%
“…GLP-1R agonists are a class of drugs targeting the incretin system that are now being investigated as potential medications to treat GDM, due to numerous recent publications showing their beneficial effects on insulin sensitivity and glucose intolerance during pregnancy [57][58][59]. However, the use of incretin drugs in pregnant people could also affect the developing fetus, highlighting the need for a better understanding of the action of these drugs during such a critical time period for offspring brain development.…”
Section: Plos Onementioning
confidence: 99%